Calibrated Automated Thrombinography (CAT), a Tool to Identify Patients at Risk of Bleeding during Anticoagulant Therapy: A Systematic Review - Zwaveling, Suzanne; Bloemen, Saartje; de Laat, Bas; ten Cate, Hugo; ten Cate-Hoek, Arina (TH Open, 2018)
Background Bleeding is a feared adverse event during anticoagulant treatment. In patients on vitamin K antagonists, most bleedings occur with the international normalized ratio (INR) in the therapeutic range. Currently, identification of high-risk patients via laboratory methods is not reliable. In this systematic review, we assessed the ability of calibrated automated thrombin generation (CAT-TG) to predict bleeding in patients on anticoagulant treatment.Methods A systematic search was executed in three databases: Medline, Embase, and Cochrane.Results Seven studies were included; two were of good methodological quality. One study showed that patients on warfarin with INRs in range (2–3) admitted for hemorrhage (n = 28), had lower CAT-TG levels (endogenous thrombin potential [ETP]: 333 ± 89 nM/min) than patients on warfarin admitted for other reasons (ETP: 436 ± 207 nM/min; p < 0.001). Another study found no difference in ETP or peak levels between bleeding and nonbleeding patients in PPP or PRP. When measured in whole blood, both levels were significantly lower in patients with bleeding compared with nonbleeding patients (median [interquartile range, IQR] ETP: 182.5 [157.2–2,847 nM/min] vs. median [IQR] ETP: 256.2 [194.9–344.2 nM/min]; p < 0.001) and median [IQR] peak: 23.9 [19.6–41.8 nM] vs. median [IQR] peak: 39.1 [24.9–53.2 nM]; p < 0.05). From the remaining studies, four suggested that CAT-TG is more sensitive in detecting hemostatic abnormalities than INR and one article found ETP and INR to be equally useful. However, insufficient data were provided to validate these conclusions.Conclusion Studies investigating the direct association between decreased CAT-TG values and hemorrhagic events are rare. Therefore, the clinical consequences of low CAT-TG values remain to be further investigated.
Keywords: thrombin generation; vitamin K antagonist; bleeding; oral anticoagulant